Efficacy of Direct-acting Antivirals for Chronic Hepatitis C Virus Infection in People Who Inject Drugs or Receive Opioid Substitution Therapy: A Systematic Review and Meta-analysis. (12th September 2019) - Graf, Christiana; Mücke, Marcus M; Dultz, Georg; Peiffer, Kai-Henrik; Kubesch, Alica; Ingiliz, Patrick; Zeuzem, Stefan; Herrmann, Eva; Vermehren, Johannes
Abstract: Background: Treatment uptake for hepatitis C virus (HCV) infection in people who inject drugs (PWID) and patients on opioid substitution therapy (OST) is still low despite treatment guidelines that advocate the use of direct-acting antivirals (DAAs) in all patients. Our aim in this review was to investigate treatment outcomes among PWID and patients on OST in comparison to control cohorts. Methods: A search of Embase, Medline, PubMed, and Web of Science (from October 2010 to March 2018) was conducted to assess sustained virologic response (SVR), discontinuation rates, adherence, and HCV reinfection in PWID and patients on OST. Results: We identified 11 primary articles and 12 conference abstracts comprising 1702 patients on OST, 538 PWID, and 19 723 patients who served as controls. Among patients on OST, the pooled SVR was 90% (95% confidence interval [CI], 87% to 93%) and pooled treatment discontinuation rate was 7% (95% CI, 4% to 11%). Similarly, the pooled SVR was 88% (95% CI, 80% to 93%) in PWID and the pooled treatment discontinuation rate was 9% (95% CI, 5% to 15%). There was no significant difference regarding pooled rates of SVR, adherence, and discontinuation between patients on OST and controls as well as between PWID and controls. HCV reinfection rates among patients on OST ranged from 0.0 to 12.5 per 100 person-years. Conclusions: HCV treatment outcomes in PWID and patients on OST are similar to those in patients without a history of injecting drugs, supporting current guideline recommendations to treat HCV in these patient populations. Abstract : Response to Direct-acting Antivirals therapy among People Who Inject Drugs and patients on Opioid Subsitution Therapy is comparable to those with no current or former drug use. Access to treatment should be expanded in these patient cohorts.